2011
DOI: 10.1007/s00421-011-1918-z
|View full text |Cite
|
Sign up to set email alerts
|

Acute effects of walking in forest environments on cardiovascular and metabolic parameters

Abstract: We previously found that forest environments reduced stress hormones such as adrenaline and noradrenaline and showed the relaxing effect both in male and female subjects. In the present study, we investigated the effects of walking under forest environments on cardiovascular and metabolic parameters. Sixteen healthy male subjects (mean age 57.4 ± 11.6 years) were selected after obtaining informed consent. The subjects took day trips to a forest park in the suburbs of Tokyo and to an urban area of Tokyo as a co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
201
1
20

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 197 publications
(236 citation statements)
references
References 31 publications
14
201
1
20
Order By: Relevance
“…Dayawansa et al [22] demonstrated, via cedrol oil inhalation by humans, a reduced sympathetic nerve activity and an increased parasympathetic tone, thus presenting a consequent increase in the baroreflex sensitivity. Such results can be associated with Li et al [23], who found a significant effect of a 2 hours walk in a forest park on BP reduction, corroborating the current outcomes, demonstrating that the interaction between aerobic exercise and eucalyptus essential oil attenuates SBP reactivity to induced stress. However, according to the current study, a 15 minutes run/walk at moderate intensity was enough.…”
Section: Discussionsupporting
confidence: 91%
“…Dayawansa et al [22] demonstrated, via cedrol oil inhalation by humans, a reduced sympathetic nerve activity and an increased parasympathetic tone, thus presenting a consequent increase in the baroreflex sensitivity. Such results can be associated with Li et al [23], who found a significant effect of a 2 hours walk in a forest park on BP reduction, corroborating the current outcomes, demonstrating that the interaction between aerobic exercise and eucalyptus essential oil attenuates SBP reactivity to induced stress. However, according to the current study, a 15 minutes run/walk at moderate intensity was enough.…”
Section: Discussionsupporting
confidence: 91%
“…The potential health and wellbeing benefits provided by sensory experiences from the smells of nature must be taken into account, especially the smell of fresh air [44,49], wet earth [41,45], trees [54,55] and wild fruits [44]. There are potentially healthful flora settings that should be identified, considering the presence of native flowers [56,57], the degree of plant biodiversity [49,58,59] and the presence of grassland [60] and trees [44,45,49,61].…”
Section: Ecosystem's Health Potential (Ehp)mentioning
confidence: 99%
“…A meta-analysis revealed that a walk/run in a natural environment, (e.g. public parks) provides more psycho-emotional benefits, such as revitalisation and feelings of tranquillity, in comparison to exercising in a synthetic environment, such as indoors or in built environments [11]. Therefore, green PA has been increasingly recognised as providing important positive contributions to health and wellbeing and may comprise a valuable treatment for mental health problems, acting as a buffer against the development of depression and anxiety disorders [13].…”
Section: Potential Benefits Of Green Physical Activitymentioning
confidence: 99%